Chondroid syringoma. Case presentation - Tunia María Sánchez Ramos; Joaquín Juan Urbizo Vélez; Dailín Urbizo Obiol (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Chondroid syringoma or mixed tumour is usually a benign neoplasia, constituting 0.01% of primary tumours of the skin. This is analogous to mixed tumour (Pleomorphic adenoma) of salivary gland. The diagnosis is only histopathologically. Objective: To present a patient with a diagnosis not very common of chondroid syringoma, where it is highlighted as differential diagnosis among the head and neck skin tumours. Case presentation: Is presented a case of a female patient; 45 years old, that arrived to the consulting room showing a subcutaneous nodule on the right genial region, it appeared as an asymptomatic slow-growing small mass, rounded, well bounded, mobile of soft and firm consistence, of several months of evolution, as a single lesion. The diagnosis was a chondroid syringoma or skin mixed tumour. Conclusions: It is an interesting case because it has a low frequency. It is important bear in mind this entity in the differential diagnosis of head and neck skin tumours. Despite being a benign tumour it is necessary to monitor patients, because even though it is uncommon, some cases have been reported with a malignant behaviour.  Keywords: Syringoma Chondroid, mixed tumour, skin, histopathology diagnosis, head, neck.